Social and pedagogical training in the system of professional training of social teachers to work with teenagers of "risk group" - Пахомова, Л. (Київський національний університет імені Тараса Шевченка, 2018)
The article highlights some aspects of the professional training of social pedagogues for working with "risk groups" adolescents, in particular, in terms of forming constructive interaction skills and positive life experiences in them; the author also highlights the issues of mastering the future specialists of the methodology of carrying out social pedagogical training with this category of children. The concept of "adolescents of the risk group", "training", "socio-pedagogical training" is specified. Particular attention is paid to the coverage of the content of socio-pedagogical training in the system of vocational training of social teachers.

У статті висвітлено окремі аспекти професійної підготовки соціальних педагогів до роботи з підлітками "групи ризику", зокрема в аспекті формування в них навичок конструктивної взаємодії та позитивного життєвого досвіду. Авторка також висвітлює питан- ня освоєнням майбутніми фахівцями методики проведення соціально-педагогічного тренінгу з цією категорією дітей. Уточнено по- няття "підлітки групи ризику", "тренінг", "соціально-педагогічний тренінг". Особливу увагу приділено висвітленню змісту соціально- педагогічного тренінгу у системі професійної підготовки соціальних педагогів.
Соціально-педагогічний тренінг у системі професійної підготовки соціальних педагогів до роботи з підлітками "групи ризику"
Keywords: підготовка соціальних педагогів; підлітки групи ризику; тренінг; соціально-педагогічний тренінг.; preparation of social teachers; adolescents of risk group; training; social-pedagogical training.